Analyzing students’ conceptions in simple electric circuits topic using four-tier diagnostic test - Nuriyah, Syifa; Winarno, Nanang; Kaniawati, Ida; Fadly, Wirawan; Sujito, Sujito (Journal of Research in Instructional, 2024)
The research was conducted to analyze the level of students' conceptions, common misconceptions of students, and to compare the misconceptions between female and male students. This study uses a survey research design. This study involved 207 students with 94 male and 113 female students from five schools in Bandung and Cimahi City, West Bandung, West Java Province, Indonesia.   The results showed 35.8% of students at the level of lack of knowledge, 30.6% misconception, 6.8% false negative, 15.2% false positive, and 11.6% scientific knowledge. Students' misconceptions are considered significant because they show >10% of all subtopics, especially in sub-topic parallel series. Based on the analysis, men and women don't have significant differences in misconceptions. It's better for further research to pay more attention to the participants, which students who can take the test seriously.